Effect of maternal migration on under-five mortality in the Navrongo HDSS area - George Wak; Samuel Oladokun; Sulemana Abubakari; Joyce Komesuor; Patrick Ansah; Stephen Kwankye (BMC, 2024)
Abstract Introduction Mortality under five years is an important indicator and a significant index for assessing the health and general wellbeing of a country. Even though global efforts to reduce under-five mortality have yielded some positive results, the rates are still high in most low- and middle-income countries. There is general consensus that migration and its associated remittances alleviate poverty at the rural places of origin. This tends to improve household living standards and leads to improvement in child health and survival. This paper seeks to investigate the impact of maternal migration on under-five mortality in two districts in the Upper East Region of Ghana. Methods This study used data from the Health and Demographic Surveillance System (HDSS) of the Navrongo Health Research Centre (NHRC) in Ghana. All children (20,990) born in the study area between 2000 and 2014 were included in the analysis. The outcome variable in the analysis was the survival status of the children (dead or alive). The main independent variable is migration status of the mothers (migrants and non-migrants). The Proportional Hazard Model, with a Weibull distribution, was used to examine the effect of the independent variables on the survival outcomes of the children. Results The results showed that children of migrant (in-migrant or return migrant) mothers are 49% less likely to die compared with children of non-migrant mothers [aOR = 0.513; (CI = 0.451-0585)]. In terms of migration duration before return, survival benefit was highest for children whose mothers had been away for one year and more. Other factors that were associated with increased risk of under-five mortality include children of mothers without education, children of mothers age 15-19 years, children born outside health facility, first order births, multiple births and children without grandmothers in their households. Conclusion The study has established that maternal migration, irrespective duration, contribute to child survival. Specifically, children of migrant mothers have a better survival chance than children of non-migrant mothers. To improve child survival in these poor rural settings, we recommend the promotion of conducive migration opportunities to enable women to earn some income to support their households in terms of childcare and survival.